Creation of a Poetry Anthology Based on Traditional Sundanese Culinary as Nontextual Reading Material to Increase Literary Appreciation of High School Students - Annisa Vitriya Abdullah; Sumiyadi Sumiyadi; Rudi Adi Nugroho (Universitas Muhammadiyah Malang, 2025)
The low interest in reading and students' appreciation of poetry at the high school level is an essential issue in learning literature at school. Poetry material is considered abstract and non-contextual, which makes it difficult for students to understand and appreciate its content and values. This research aims to create an anthology of thematic poetry based on traditional Sundanese Tatar cuisine that pays attention to aesthetic values, poetic language, and cultural content relevant to high school students' psychological and social development. The method used is research-based creation research with a qualitative approach. Data was obtained through observation, interviews with teachers and students, and documentation of the creative process and the results of poetry products. The study results show that poems that raise local culinary themes can increase students' attraction and emotional involvement with literary texts. The poetic language that uses everyday diction and sensory imagery has been proven to facilitate understanding while strengthening students' aesthetic experiences. In addition, students show a greater interest in exploring local culture through poetry, which has a positive impact on increasing literary appreciation and meaning. Thus, the creation of this culinary-based poetry anthology is not only a creative solution to students' low interest in poetry but also contributes to the preservation of local culture and the development of literary teaching materials that are communicative, contextual, and support meaningful learning.